The Effect of Potassium and Gibberellic Acid on Some Characteristics and Yield Components of Black Seed Plant (Nigella sativa L.) (Journal of the College of Basic Education, 2022)
The experiment was carried out using plastic pots in the uncovered plastic house of the Department of Science _ College of Basic Education / Al-Mustansiriya University for the growing season 2014-2015 to study the effect of potassium and gibberellic acid on some characteristics and yield components of the black seed plant (Nigella sativa L). The experiment was conducted according to a completely randomized design. Completely Randomized Design (CRD) as a factorial experiment with three replications for each treatment, and the Least Significant Difference (L.S.D.) test at the probability level of 0.05 was used to compare the mean of the treatments.